Active layer of organic solar cell, organic solar cell device, preparation method and application

By introducing the solid additive DTDF into the active layer of the organic solar cell, the problem of difficult control of the morphology of the active layer is solved, and more efficient carrier transmission and more stable battery performance are achieved.

CN119677289APending Publication Date: 2025-03-21DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411741172.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing organic solar cells, it is difficult to form an ideal active layer morphology, resulting in a decrease in device stability and repeatability, and the residues of high boiling points of solvent additives are difficult to remove.

Method used

The solid additive DTDF is introduced into the active layer to promote the aggregation and accumulation of donor/acceptor materials, improve the crystallinity and phase separation size, and improve the nano-scale morphology of the active layer.

Benefits of technology

It effectively improves the carrier transmission speed and charge mobility, improves the photoelectric conversion efficiency and stability, and significantly improves the short-circuit current and filling factor of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677289A_ABST
    Figure CN119677289A_ABST
Patent Text Reader

Abstract

The invention provides an active layer of an organic solar cell, an organic solar cell device, a preparation method and an application. The organic solar cell active layer comprises a donor material, an acceptor material and a solid additive, and the solid additive is DTDF. By adding the DTDF in the active layer, the blended film morphology of the active layer can be effectively regulated and controlled, the accumulation of donor and acceptor molecules is promoted, the crystallinity is enhanced, the formation of a relatively good phase separation size is promoted, an efficient carrier transport channel is established, the separation and collection efficiency of carriers is improved, and the photoelectric conversion efficiency of an organic solar cell device is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of organic solar cells, and in particular relates to an organic solar cell, an active layer doped with a solid additive, and a preparation method and application thereof. Background Art

[0002] At present, the demand for energy in all aspects of human society is growing at an alarming rate. Human beings urgently need to solve the problem of energy shortage. Therefore, humans are very concerned about renewable energy. Among renewable energy, solar energy is the most abundant energy in the world. Organic solar cell photovoltaic technology is considered to be the most promising technology in the 21st century. Organic solar cells have the advantages of low cost, good flexibility, translucency, and suitable for roll-to-roll mass production. Due to its unique material properties, it has shown broad application prospects in the fields of visible transparent windows, flexible wearable devices, building-integrated photovoltaics, etc.

[0003] Since important processes such as carrier transport and separation, charge transport and recombination in organic solar cells are closely related to their morphology, it is particularly important to finely control the morphology of organic solar cells. The morphology of the active layer is a key factor affecting the efficiency and stability of the device. The ideal active layer morphology refers to the interpenetrating network structure formed between the donor and the acceptor through the active layer, which is conducive to improving the exciton dissociation efficiency, reducing the recombination of carriers, and improving the photoelectric conversion efficiency of the device. However, since the donor / acceptor materials usually have different aggregation characteristics and miscibility with the processing solvent, it is difficult to form an ideal active layer morphology. Therefore, in order to obtain high-performance organic solar cells, appropriate strategies need to be adopted to optimize the morphology of the active layer. Among various morphology optimization strategies, the introduction of additional additives is considered to be a particularly simple and effective method to achieve the desired morphology. The most representative solvent additives are 1-chloronaphthalene (CN) and 1,8-diiodooctane (DIO). However, these additives have a high boiling point and the residual small amount of additives cannot be completely removed, which usually leads to reduced stability and repeatability of the device. Therefore, there is an urgent need to find a new additive that can effectively solve the above problems and improve battery performance.

[0004] In recent years, solid additives have been widely used in organic solar cells due to their high crystallinity and volatility. The charge carrier mobility of organic solar cells treated with solid additives and thermal annealing is greatly improved, which makes charge extraction faster, prolongs the life of carriers and reduces charge recombination, significantly improving the photoelectric conversion efficiency of organic solar cells. At the same time, solid additives will volatilize from the active layer after thermal annealing, thereby greatly enhancing the stability of organic solar cells. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides an active layer of an organic solar cell, an organic solar cell device, and a preparation method and application thereof. The present invention introduces a solid additive DTDF into the active layer of the organic solar cell, thereby promoting more ordered aggregation and accumulation of donor / acceptor (D / A) molecules, higher crystal strength, and more suitable phase separation size, so that the nanoscale morphology of the active layer is effectively improved, faster carrier transport, more balanced charge mobility, higher dissociation / collection efficiency, and suppression of non-radiative recombination are obtained, thereby effectively improving the short-circuit current (Jsc) and fill factor (FF) of the solar cell device, and significantly improving the photoelectric performance of the solar cell.

[0006] The technical solution provided by the present invention is as follows:

[0007] The present invention provides an active layer of an organic solar cell, wherein the active layer comprises a donor material, an acceptor material and a solid additive; the solid additive is DTDF, and the structural formula of the DTDF is: .

[0008] Furthermore, the donor material includes PM6 or D18; the acceptor material includes Y6.

[0009] Specifically, the structural formulas of the donor materials PM6, D18 and the acceptor material Y6 are as follows: ; .

[0010] Furthermore, the mass ratio of the donor material to the acceptor material is 1:1.2.

[0011] Furthermore, the amount of the solid additive added is 10-50% of the mass of the receptor material.

[0012] Preferably, the amount of the solid additive added is 30% of the mass of the receptor material.

[0013] Furthermore, the thickness of the active layer is 100-150 nm.

[0014] The present invention provides the use of the active layer of the organic solar cell described above in the preparation of an organic solar cell device.

[0015] The invention provides an organic solar cell device, comprising an ITO glass sheet, a hole PEDOT:PSS transport layer, the above-mentioned active layer, an electron PFN-Br transport layer and a metal Ag cathode layer which are sequentially arranged from bottom to top.

[0016] The present invention provides a method for preparing the above-mentioned organic solar cell device, comprising the following steps: A hole PEDOT:PSS transport layer was prepared on an ITO glass sheet; Dissolving a donor material, an acceptor material and a solid additive in an organic solvent to prepare a composite solution, and spin-coating the composite solution on the hole PEDOT:PSS transport layer, annealing and then cooling to form an active layer; preparing an electron PFN-Br transport layer on the active layer; A metal Ag cathode layer is prepared on the electron PFN-Br transport layer.

[0017] Furthermore, the total concentration of the composite solution is 16-18 mg / mL.

[0018] Furthermore, the organic solvent is chloroform; the spin coating speed is 3000-5000 r / min, and the spin coating time is 30-50s; the annealing temperature is 100-150°C, and the annealing time is 15-20 min.

[0019] Beneficial Effects

[0020] 1. The present invention provides an active layer of an organic solar cell, wherein the active layer contains a solid additive DTDF, which has a simple structure and good stability, and is well miscible with the donor and acceptor materials in the active layer. Secondly, the solid additive DTDF is introduced into the active layer, which promotes the aggregation and molecular stacking between the donor and acceptor, improves the crystallinity, and forms a favorable phase separation size, effectively improving the morphology of the active layer.

[0021] 2. The solid additive is added to the active layer of the organic solar cell of the present invention, so that the short-circuit current density and fill factor of the organic solar cell are greatly improved, thereby improving the photoelectric conversion efficiency of the organic solar cell. In addition, the solid additive has good universality, is easy to prepare, and has low production cost.

[0022] 3. The present invention adds a solid additive DTDF to the active layer of the organic solar cell. Based on the PM6:Y6 system, after adding the solid additive DTDF, the photoelectric conversion efficiency of the organic solar cell is increased from 13.39% to 15.06%. Based on the D18:Y6 system, after adding the solid additive DTDF, the photoelectric conversion efficiency of the organic solar cell is increased from 13.79% to 15.61%. Based on the PM6:Y6 system and the D18:Y6 system, the photoelectric conversion efficiency of organic solar cells is improved. Therefore, the solid additive DTDF has good universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1This is the JV curve of the organic solar cell device in Example 1 of the present invention.

[0024] Figure 2 EQE curve of the organic solar cell device in Example 1 of the present invention.

[0025] Figure 3 This is the JV curve of the organic solar cell device in Example 2 of the present invention.

[0026] Figure 4 EQE curve of the organic solar cell device in Example 2 of the present invention.

[0027] Figure 5 : Thermogravimetric analysis (TGA) curves of the solid additive DTDF in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0028] In order to describe the present invention more clearly, the present invention is further described below in conjunction with embodiments and drawings. The examples described below are exemplary and are only used to help understand the present invention, and cannot be used as a limitation of the present invention.

[0029] The reagents and materials described in the following examples can be obtained from conventional markets unless otherwise specified.

[0030] An embodiment of the present invention provides an active layer of an organic solar cell, wherein the active layer comprises a donor material, an acceptor material and a solid additive; the solid additive is DTDF, and the structural formula of the DTDF is: .

[0031] In this embodiment, the donor material includes PM6 or D18; the acceptor material includes Y6.

[0032] In this embodiment, the mass ratio of the donor material to the acceptor material is 1:1.2.

[0033] In this embodiment, the amount of the solid additive added is 10-50% of the mass of the receptor material.

[0034] Preferably, the amount of the solid additive added is 30% of the mass of the receptor material.

[0035] In this embodiment, the thickness of the active layer is 100-150 nm.

[0036] The embodiment of the present invention provides the use of the active layer of the organic solar cell described above in the preparation of an organic solar cell device.

[0037] An embodiment of the present invention provides an organic solar cell device, comprising an ITO glass sheet, a hole PEDOT:PSS transport layer, the above-mentioned active layer, an electron PFN-Br transport layer and a metal Ag cathode layer arranged in sequence from bottom to top.

[0038] An embodiment of the present invention provides a method for preparing the above-mentioned organic solar cell device, comprising the following steps: A hole PEDOT:PSS transport layer was prepared on an ITO glass sheet; Dissolving a donor material, an acceptor material and a solid additive in an organic solvent to prepare a composite solution, and spin-coating the composite solution on the hole PEDOT:PSS transport layer, annealing and then cooling to form an active layer; preparing an electron PFN-Br transport layer on the active layer; A metal Ag cathode layer is prepared on the electron PFN-Br transport layer.

[0039] In this embodiment, the total concentration of the composite solution is 16-18 mg / mL.

[0040] In this embodiment, the organic solvent is chloroform; the spin coating speed is 3000-5000 r / min, and the spin coating time is 30-50 s; the annealing temperature is 100-150° C., and the annealing time is 15-20 min.

[0041] In this embodiment, the preparation of the hole PEDOT:PSS transport layer on the ITO glass sheet specifically includes: spin coating the filtered PEDOT:PSS aqueous solution on the ITO glass sheet, annealing and cooling to form a hole transport layer; the spin coating speed is 3000~5000 r / min, and the spin coating time is 30~50 s; the annealing temperature is 100~150℃, and the annealing time is 15~20 min.

[0042] In this embodiment, preparing an electron PFN-Br transport layer on the active layer specifically includes: dissolving PFN-Br in methanol to prepare a solution with a concentration of 0.5 mg / ml and then spin coating the solution on the active layer to form an electron transport layer; the spin coating speed is 3000~5000 r / min, and the spin coating time is 30~50 s.

[0043] Example 1

[0044] The present invention provides an organic solar cell device, which adopts an upright device structure. The structural device comprises an ITO glass sheet, a hole PEDOT:PSS transport layer, a PM6:Y6 active layer containing a solid additive, an electron PFN-Br transport layer and a metal Ag cathode layer, which are arranged in sequence from bottom to top.

[0045] This embodiment provides the preparation of an organic solar cell having an active layer of PM6:Y6 containing a solid additive, and the preparation steps are as follows:

[0046] (1) Cleaning of ITO glass substrate: First, clean the ITO glass substrate with detergent for 10 minutes, then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence, with the ultrasonic cleaning time being 15 minutes each. Then, transfer it to an ultra-clean bench and use a nitrogen gun to blow dry the residual reagents attached to the surface of the ITO base glass. Then, transfer it to an oven for drying, and finally place it in a UV ozone treatment box for UV treatment for 15 minutes.

[0047] (2) Preparation of hole transport layer: Take out the low-temperature refrigerated PEDOT:PSS aqueous solution from the refrigerator, and then filter it with a water-soluble filter. In air, spin coat the filtered PEDOT:PSS aqueous solution on a spin coater at a speed of 5000 r / min on the cleaned ITO glass substrate for 40 s. Then take out the substrate and place it on a heating table at 150°C for annealing for 15 min. Then cool it at room temperature for 10 min to obtain a hole transport layer with a thickness of about 30 nm. Then transfer the substrate to a glove box with a N2 atmosphere.

[0048] (3) Preparation of active layer: First, weigh the required active layer materials on a weighing table, weigh PM6 and Y6 according to a mass ratio of 1:1.2, and weigh the solid additive DTDF according to the acceptor mass ratio. Then, in a glove box with N2 atmosphere, use chloroform (CF) as a solvent to prepare a mixed solution with a concentration of 16 mg / ml, and then place it on a heating table at 40°C and stir for 3~4 hours to fully dissolve the solution. Then, the active layer solution was spin-coated on the hole transport layer at a speed of 3000 r / min for 35 seconds to form a uniform blended film. Then, the substrate was placed on a heating table at 100°C for annealing for 10 minutes. After cooling for 10 minutes, an active layer with a thickness of 100~150 nm was obtained.

[0049] (4) Preparation of electron transport layer: First, weigh the material PFN-Br required for the electron transport layer. Then, in a glove box with a N2 atmosphere, use methanol as the solvent to prepare a solution with a solubility of 0.5 mg / ml. After sufficient stirring to dissolve, spin coat the solution on the active layer at a speed of 3000 r / min for 30 seconds to obtain an electron transport layer with a thickness of about 5 nm.

[0050] (5) Preparation of cathode: In a glove box with N2 atmosphere, transfer the substrate with electron transport layer spin-coated to a vacuum evaporation device and -6 The organic solar cell is prepared by evaporating an Ag electrode with a thickness of 100 nm under a pressure of 1.3 Pa.

[0051] (6) Packaging: In a glove box with N2 atmosphere, the prepared organic solar cell was packaged with UV curable resin.

[0052] The photovoltaic performance of an organic solar cell device with an active layer of PM6:Y6 containing a solid additive is tested in the embodiment of the present invention:

[0053] Simulate sunlight at AM1.5 (light intensity 100mw / cm 2 ) under the condition of irradiation, the current-voltage curve (JV curve, such as Figure 1 The device performance parameters are shown in Table 1. As can be seen from Table 1, as the proportion of solid additives (the mass proportion of the acceptor) gradually increases, the photoelectric conversion efficiency of the device shows a trend of first increasing and then decreasing. It can be seen that the device has the best performance when the solid additive addition ratio is 30wt%. After post-treatment, its short-circuit current density (J sc ) is 25.18 mA / cm 2 , open circuit voltage (V oc ) is 0.817V, the fill factor (FF) is 73.2%, and the photoelectric conversion efficiency (PCE) is 15.06%. The EQE curves of devices with solid additives and those without additives (such as Figure 2 The short-circuit current density calculated by integration is basically consistent with the short-circuit current density result of the JV curve.

[0054] Table 1 Performance parameters of organic solar cell devices based on PM6:Y6 system

[0055]

[0056] In Table 1, a represents an organic solar cell device without post-treatment, and b represents an organic solar cell device after annealing at 100°C for 10 min.

[0057] Example 2

[0058] The present invention provides an organic solar cell device, which adopts an upright device structure. The structural device comprises an ITO glass sheet, a hole PEDOT:PSS transport layer, an active layer of D18:Y6 containing a solid additive, an electron PFN-Br transport layer and a metal Ag cathode layer, which are arranged in sequence from bottom to top.

[0059] This embodiment provides the preparation of an organic solar cell having an active layer of D18:Y6 containing a solid additive, and the preparation steps are as follows:

[0060] (1) Cleaning of ITO glass substrate: First, clean the ITO glass substrate with detergent for 10 minutes, then ultrasonically clean it with deionized water, acetone, and isopropanol in sequence, with the ultrasonic cleaning time being 15 minutes each. Then, transfer it to an ultra-clean bench and use a nitrogen gun to blow dry the residual reagent attached to the surface of the ITO base glass, then transfer it to an oven for drying, and finally place it in a UV ozone treatment box for UV treatment for 15 minutes.

[0061] (2) Preparation of hole transport layer: Take out the low-temperature refrigerated PEDOT:PSS aqueous solution from the refrigerator, and then filter it with a water-soluble filter. In air, spin coat the filtered PEDOT:PSS aqueous solution on a spin coater at a speed of 5000 r / min on the cleaned ITO glass substrate for 40 s. Then take out the substrate and place it on a heating table at 150°C for annealing for 15 min. Then cool it at room temperature for 10 min to obtain a hole transport layer with a thickness of about 30 nm. Then transfer the substrate to a glove box with a N2 atmosphere.

[0062] (3) Preparation of active layer: First, weigh the required active layer materials on a weighing table, weigh D18 and Y6 at a mass ratio of 1:1.2, and weigh the following according to the receptor mass ratio: Figure 1 The solid additive shown was then prepared into a mixed solution with a concentration of 18 mg / ml in a glove box with N2 atmosphere using chloroform (CF) as a solvent, and then placed on a heating table at 40°C and stirred for 3-4 hours to fully dissolve the solution. The active layer solution was then spin-coated on the hole transport layer at a speed of 3000 r / min for 35 seconds to form a uniform blended film, obtaining an active layer with a thickness of 100-150 nm.

[0063] (4) Preparation of electron transport layer: First, weigh the material PFN-Br required for the electron transport layer. Then, in a glove box with a N2 atmosphere, use methanol as the solvent to prepare a solution with a solubility of 0.5 mg / ml. After sufficient stirring to dissolve, spin coat the solution on the active layer at a speed of 3000 r / min for 30 seconds to obtain an electron transport layer with a thickness of about 5 nm.

[0064] (5) Preparation of cathode: In a glove box with N2 atmosphere, transfer the substrate with electron transport layer spin-coated to a vacuum evaporation device and - 6 The organic solar cell is prepared by evaporating an Ag electrode with a thickness of 100 nm under a pressure of 1.3 Pa.

[0065] (6) Packaging: In a glove box with N2 atmosphere, the prepared organic solar cell was packaged with UV curable resin.

[0066] The photovoltaic performance of an organic solar cell device with an active layer of D18:Y6 containing a solid additive is tested in the embodiment of the present invention:

[0067] Simulate sunlight at AM1.5 (light intensity 100mw / cm 2 ) under the condition of irradiation, the current-voltage curve (JV curve, such as Figure 3 After adding solid additives, the short-circuit current density (J sc ) is 25.26 mA / cm 2 , open circuit voltage (V oc ) is 0.878V, the fill factor (FF) is 70.4%, and the photoelectric conversion efficiency (PCE) of the device is 15.61%. The performance parameters of the tested device are shown in Table 2. The EQE curves of the devices with and without solid additives are tested (such as Figure 4 The short-circuit current density calculated by integration is basically consistent with the short-circuit current density result of the JV curve.

[0068] Table 2 Performance parameters of organic solar cell devices based on D18:Y6 system

[0069]

[0070] It can be seen from Table 1 and Table 2 that the use of the solid additives described in the present invention in the active layer of organic solar cells of different systems effectively improves the short-circuit current density and fill factor, further improving the photoelectric conversion efficiency of organic solar cells. The results show that solid additives can effectively improve the photovoltaic performance of the active layers PM6:Y6 and D18:Y6 of organic solar cells, and have good universality. It is proved that the use of DTDF as a solid additive to effectively regulate the morphology of organic solar cell blended films and improve the photoelectric conversion efficiency of organic solar cells has great potential.

[0071] The specific examples described above are only preferred embodiments of the present invention and cannot be used as limitations of the present invention. It should be understood by those skilled in the art that improvements, replacements and modifications can be made based on the present invention as required without departing from the principles of the present invention, and these improvements, replacements and modifications should also fall within the scope of protection of the claims of the present invention.

Claims

1. An active layer of an organic solar cell, characterized in that: The active layer comprises a donor material, an acceptor material and a solid additive; the solid additive is DTDF, and the structural formula of the DTDF is: 。 2. The active layer of the organic solar cell according to claim 1, characterized in that: The donor material includes PM6 or D18; the acceptor material includes Y6.

3. The active layer of the organic solar cell according to claim 1, characterized in that: The mass ratio of the donor material to the acceptor material is 1:1.

2.

4. The active layer of the organic solar cell according to claim 1, characterized in that: The amount of the solid additive added is 10-50% of the mass of the receptor material.

5. The active layer of the organic solar cell according to claim 1, characterized in that: The thickness of the active layer is 100-150 nm.

6. Use of the active layer of the organic solar cell according to any one of claims 1 to 5 in the preparation of an organic solar cell device.

7. An organic solar cell device, characterized in that: The invention comprises an ITO glass sheet, a hole PEDOT:PSS transport layer, an active layer according to any one of claims 1 to 5, an electron PFN-Br transport layer and a metal Ag cathode layer which are arranged in sequence from bottom to top.

8. A method for preparing an organic solar cell device according to claim 7, characterized in that: The following steps are involved: A hole PEDOT:PSS transport layer was prepared on an ITO glass sheet; Dissolving a donor material, an acceptor material and a solid additive in an organic solvent to prepare a composite solution, and spin-coating the composite solution on the hole PEDOT:PSS transport layer, annealing and then cooling to form an active layer; preparing an electron PFN-Br transport layer on the active layer; A metal Ag cathode layer is prepared on the electron PFN-Br transport layer.

9. The preparation method according to claim 8, characterized in that: The total concentration of the composite solution is 16-18 mg / mL.

10. The preparation method according to claim 8, characterized in that: The organic solvent is chloroform; the spin coating speed is 3000-5000 r / min, and the spin coating time is 30-50 s; the annealing temperature is 100-150° C., and the annealing time is 15-20 min.